The influence of fraud prevention mechanisms on fraud awareness in the federal ministries in Malaysia / Noorfarhana Wahiza Abdul Latif … [et al.] - Abdul Latif, Noorfarhana Wahiza; Hasnan, Suhaily; Mohamed Hussain, Alfiatul Rohmah; Mohd Ali, Mazurina (Universiti Teknologi MARA, 2021)
This study examined the extent of fraud prevention mechanisms that influence the awareness of curbing the occurrence of fraudulent activities in public sector organisations, particularly the Federal Ministries in Malaysia. The key factors in this study thereby attributed as the fraud prevention mechanisms that influenced by ethical leadership, internal control system, and fraud prevention programmes. Following this, the Agency Theory was employed to guide the study. A survey was conducted among the officers of various Federal Ministries who were sampled via the purposive sampling method and yielded 210 total responses. The results showed that ethical leadership and the implementation of a virtuous internal control system ranked as the most effective fraud prevention mechanism that influenced their awareness towards curbing the occurrence of fraud. A regression analysis further revealed that the fraud prevention programmes were not statistically significant in influencing awareness of fraud. The main value of this paper is the effect of fraud prevention mechanisms; namely, ethical leadership, internal control systems, and fraud prevention programmes, on awareness of fraud amongst officers in the Federal Ministries in Malaysia. The findings of this study provide useful insights for the Federal government to improve and reconsider current fraud prevention mechanisms, especially fraud prevention programmes to improve awareness of fraud and recover public trust.